âGULALIâ GANTUNGAN ANTI LALI SEBAGAI PENDETEKSI - Hauna, Zahra Inatsa; Pratiwi, Siska; Dewi, Sasti Dwi Tungga; Wahyudin, Muhammad; Susanto, Kusnahadi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Increasingly sophisticated technology enables the creation of material and goods with very small size and flexible. The problems that arise with such a small item storage is negligence in causing impaired daily activities. Solutions to overcome these problems are made of GULALI (Gantungan Anti Lali) which can detect small sized goods with frequency. GULALI is containt of a remote control (transmitter) and the hanger as the recipient (receiver) equipped with speakers mounted on a small sized objects. GULALI can detect the presence of the goods within 5 m in horizontal and vertical direction. Â Keywords: Small Goods, Negligence, Frequency, GULALI